APLIKASI SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEB (SIAPDIKU) PADA SMAS HUTAMA BEKASI - Asrofi, Abdul Razak; Hariyanto, Dicky; Sunita Perangin-angin, Elvi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
In 2018 the percentage of student registrations for State High Schools was 73.27% and for Private High Schools amounted to 26.73% to be the focus in the design of applications for admission of new students to improve the effectiveness of PPDB in HUTAMA High Schools. The method of designing a new web-based application for student acceptance uses the waterfall method by analyzing needs by conducting observations and interviews. At this stage as a resource person, the school and students who have made the process of accepting new students. The process of designing and making programs to represent the results of needs analysis by making interface designs, software architecture, and interface interactions, as well as program implementation and testing using the black box testing method. Results from this research can be obtained by the application of new web-based student admissions that aims to summarize the processes carried out with the previous system. Prospective students can register new students online that are not limited by space so that they can register anywhere and anytime in accordance with the policies of the school. And the school that carries out data management can directly receive the results of the report and can directly carry out data management without having to do typing first.